Antimicrobial effect of chlorine dioxide on Actinobacillus actinomycetemcomitans in diabetes mellitus rats treated with insulin - Tantin Ermawati; Kwartarini Murdiastuti (Universitas Airlangga, 2012)
Background: Periodontitis is a chronic inflammatory disease of periodontal tissues. Etiology of periodontal disease includes Actinobacillus actinomycetemcomitans (A. actinomycetemcomitans) which is the most predominant disease-causing bacteria found in the gingival sulcus. Periodontitis can be exacerbated by the systemic disease, such as diabetes mellitus considered as a metabolic disease characterized by hyperglycemia due to insulin deficiency. Treatment of periodontitis is then required in patients with type I diabetes to avoid radical reaction that can not only cause bleeding, but can also prevent infection, as a result, topical antimicrobial therapy and blood glucose control are required. Topical antimicrobial chlorine dioxide is a disinfectant that is effective in killing A. actinomycetemcomitans. Purpose: This study is aimed to determine the effects of topical antimicrobial chlorine dioxide gel or rinse on the number of A. actinomycetemcomitans in DM rats treated with insulin. Methods: 20 three month old male Wistar rats with weight of 170-200 grams were divided into four groups. First, periodontitis and DM were manipulated into all groups through aloksan injection with dose of 170 mg/kg. Those rats in group I were treated with insulin and chlorine dioxide gel, those in group II were treated with insulin and chlorine dioxide rinse, those in group III were treated with insulin only, and those in group IV were without treatment. In the third and seventh weeks, the number of A. actinomycetemcomitans was measured. The data was tested by using One-Way ANOVA test followed by LSD test. Results: The study showed that chlorine dioxide gel has a greater ability in reducing the number of A. actinomycetemcomitans than chlorine dioxide rinse although both are antimicrobials. Conclusion: It can be concluded that the use of chlorine dioxide gel can more effective to decrease the number of A. actinomycetemcomitans than chlorine dioxide rinse in DM rats treated with insulin therapy. Latar belakang: <span style="font-family: